Goal programming and analytical hierarchy process approaches for sustainable plantation - Ostadhashemi, R.; Rostami Shahraji, T.; Mohammadi Limaei, S.; Roehle, H. (Caspian Journal of Environmental Sciences, 2014)
The aim of this study was to develop an optimal sustainable forest plantation based on goal programming and Analytic Hierarchy Process (AHP) methods. This study was carried out in Guilan province, north of Iran. First of all, the ecological capability of the study area for plantation establishment/maintenance was evaluated based on multi-factor method and specific ecological Makhdoum Model by means of GIS tools. Then goal programming approach as a multi criteria optimization technique was used for optimization. Therefore, ecological, economic and social aims were considered. Carbon sequestration was chosen as an ecological criterion. To estimate the total aboveground biomass and carbon content stem volume, stem biomass and crown biomass were measured using allometric equations. The net present value was also calculated using stumpage price, harvesting cost, consumer price index, annual growth, interest rate and optimal rotating. Estimated required labour for different plantation items were obtained from data base of Iranian Forests Rangelands and Watershed Management Organization. In order to achieve all purposes simultaneously, the goal programming technique was applied. Results indicated that using mathematical modeling provided a more logical set of consequences compared to using ecological modeling. The ability to change the weighting of the variables in the mathematical equations enabled decision makers to choose the optimal solution. Final results indicated that the appropriate plantation area for each species are as follow: Acer velutinum (810 ha), Alnus subcordata (348 ha), Pinus taeda (235 ha), Tilia begonifolia (165 ha), Quercus castanifolia (149 ha), Pinus nigra (110 ha) and Fraxinus excelsior (0 ha).